1987
DOI: 10.1038/330074a0
|View full text |Cite
|
Sign up to set email alerts
|

Interference with HIV-induced syncytium formation and viral infectivity by inhibitors of trimming glucosidase

Abstract: Human immunodeficiency virus (HIV), the causative agent of AIDS, infects human lymphocytes and monocytes. An interaction between the viral envelope gp 120 and CD4 protein is required to initiate an infectious cycle. HIV infection in vitro induces syncytium formation by cell-to-cell fusion; this aspect of viral cytopathogenicity is even more dependent on gp120-CD4 interactions. That gp120 is extremely heavily glycosylated (31-36 N-linked glycans per molecule), suggests involvement of N-linked glycans in the gp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
228
2
3

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(242 citation statements)
references
References 0 publications
6
228
2
3
Order By: Relevance
“…Previous studies have examined the effects of CST on HIV-1-infected cells and have shown a reduction in the formation of syncytia and virus infectivity (28,29). These reports have either assayed the effect of CST on viral replication in multiple rounds or have used cell culture supernatants containing CST as a source of virus input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have examined the effects of CST on HIV-1-infected cells and have shown a reduction in the formation of syncytia and virus infectivity (28,29). These reports have either assayed the effect of CST on viral replication in multiple rounds or have used cell culture supernatants containing CST as a source of virus input.…”
Section: Discussionmentioning
confidence: 99%
“…Following the misfolding of proteins within the ER, they undergo a degradative process, probably mediated by the cytosolic 26 S proteasome (27). The treatment of HIV-1-infected cells with ␣-glucosidase inhibitors was shown to interfere with syncytia formation (28,29). However, gp120, expressed in the presence of DNJ (13), and NB-DNJ demonstrated no difference in their abilities to bind to CD4 or to bind to T-cells (30).…”
Section: Hiv (Human Immunodeficiency Virus)-1 Env Is Displayed On Thementioning
confidence: 99%
“…HeLa cells transfected with the wild-type and 6His proviruses were grown in the presence or absence of 1 mM DMM, which inhibits mannosidase I in the Golgi apparatus, generating proteins containing only highmannose N-glycans lacking sialic acid (43). As previously noted (18), the N-glycans of the wild-type gp120 were only partially converted to the complex type, and DMM blocked this process, resulting in higher electrophoretic mobility, as marked by band a in Fig. 6B (compared to lanes 3 and 4).…”
Section: Exhibition By 6his and 9his Mutants Of Decreased Electrophormentioning
confidence: 99%
“…(Pan et al, 1983;Szumilo, Kaushal & Elbein, 1986;Campbell, Molyneux & Jones, 1987). It has since attracted considerable interest because of its antiviral activity against HIV and related viruses (Tyms et al, 1987;Sunkara, Bowlin, Liu & Sjoerdsma, 1987;Gunters et al, 1987;Walker et al, 1987). The enantiospecific synthesis of polyhydroxylated indolizidines related to castanospermine has also received much attention 0108-2701/93/020391-02506.00 …”
Section: Commentmentioning
confidence: 99%